2015
DOI: 10.1016/j.csbj.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Computing the origin and evolution of the ribosome from its structure — Uncovering processes of macromolecular accretion benefiting synthetic biology

Abstract: Accretion occurs pervasively in nature at widely different timeframes. The process also manifests in the evolution of macromolecules. Here we review recent computational and structural biology studies of evolutionary accretion that make use of the ideographic (historical, retrodictive) and nomothetic (universal, predictive) scientific frameworks. Computational studies uncover explicit timelines of accretion of structural parts in molecular repertoires and molecules. Phylogenetic trees of protein structural dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(66 citation statements)
references
References 144 publications
(270 reference statements)
1
59
0
Order By: Relevance
“…We note that in most cases the recruited parts become physically associated with the growing system, with b of Equation (2) representing the growing system and a the accreted part. Examples of accretion of these kinds are macromolecular complexes such as the ATP synthases and the ribosome [25,26]. The F-type and A/V-type synthases are multi-subunit complexes responsible for membrane-coupled energy conversion reactions.…”
Section: Memory and The Evolutionary Drivers Of Abundance Recruitmentioning
confidence: 99%
See 2 more Smart Citations
“…We note that in most cases the recruited parts become physically associated with the growing system, with b of Equation (2) representing the growing system and a the accreted part. Examples of accretion of these kinds are macromolecular complexes such as the ATP synthases and the ribosome [25,26]. The F-type and A/V-type synthases are multi-subunit complexes responsible for membrane-coupled energy conversion reactions.…”
Section: Memory and The Evolutionary Drivers Of Abundance Recruitmentioning
confidence: 99%
“…Using phylogenomic methods we have shown that the synthase complexes developed gradually by addition of structural domains, starting with the ring structures of the rotating head, followed by the central stalk (the axle), and ending with the structures that regulate their motion (the stators) [25]. Similarly, the ribosome has been shown to grow in evolution by addition of helical segments to the evolving molecules [26], complying with the principle of continuity that sustains evolutionary thinking and explaining the formation of highly sophisticated macromolecular machinery.…”
Section: Memory and The Evolutionary Drivers Of Abundance Recruitmentioning
confidence: 99%
See 1 more Smart Citation
“…Cladistic methodology has been successfully applied to the study of molecular evolution. For example, phylogenetic characters describing the length and stability of RNA helical segments or the abundance of protein structural domains in genomes have been used to build phylogenetic trees of molecules and proteomes, respectively (reviewed in Caetano-Anollés and Caetano-Anollés, 2015a). These methodologies have been recently extended to study the origin and evolution of the ribosome (Harish and Caetano-Anollés, 2012).…”
mentioning
confidence: 99%
“…The inset describes a network interaction diagram of the same junction in a different structure, again showing the h33-h34 stacked helices (redrawn from Lescoute and Westhof, 2006). Any claim that the coaxially stacked h33-h34 is a branch that “caps” an older h32 trunk is ad hoc , erases the original IF signature, and introduces a serious ambiguity (see Figure 10C and discussion in Caetano-Anollés and Caetano-Anollés, 2015a), which defeats the entire algorithmic implementation. (D) Road blocks to outward growth create multiple ribosomal origins.…”
mentioning
confidence: 99%